2010
DOI: 10.1097/cco.0b013e32833de186
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells and emerging blood biomarkers in breast cancer

Abstract: Currently, there is no role for CTCs in clinical practice. The clinical utility of CTCs and other blood biomarkers should be prospectively tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…By screening the expression levels of 754 human miRs using miR arrays in 16 breast tumor samples from 8 cases with local recurrence and 8 cases without local recurrence, Zhou and his colleagues reported that microRNA-9 could be used as a potential biomarker for breast cancer local recurrence and tumor estrogen receptor status [33]. As the stability of miRs and their detection in circulation, the miRNAs in body fluids, such as serum and plasma, open up the possibility of using them as noninvasive biomarkers in breast cancer [34,35]. MiR-497, identified from the microRNA cluster site at chromosome 17p13.1, has been reported to function as a tumor suppressor in a variety of human cancers, including non-small cell lung cancer, hepatocelluar cancer, neroblastoma, colorectal cancer and breast cancer [18,21,36-38].…”
Section: Discussionmentioning
confidence: 99%
“…By screening the expression levels of 754 human miRs using miR arrays in 16 breast tumor samples from 8 cases with local recurrence and 8 cases without local recurrence, Zhou and his colleagues reported that microRNA-9 could be used as a potential biomarker for breast cancer local recurrence and tumor estrogen receptor status [33]. As the stability of miRs and their detection in circulation, the miRNAs in body fluids, such as serum and plasma, open up the possibility of using them as noninvasive biomarkers in breast cancer [34,35]. MiR-497, identified from the microRNA cluster site at chromosome 17p13.1, has been reported to function as a tumor suppressor in a variety of human cancers, including non-small cell lung cancer, hepatocelluar cancer, neroblastoma, colorectal cancer and breast cancer [18,21,36-38].…”
Section: Discussionmentioning
confidence: 99%
“…Together with the reported strong overexpression of TROP2 on metastatic tumor cells, studies should include anti-TROP2 stainings to detect and quantify circulating tumor cells; this strategy currently mostly relies on anti-EpCAM stainings (Criscitiello et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Kidney cancer cells may escape detection by surface marker-based methods, such as those based on epithelial cell adhesion molecule (EpCAM). 22 The conundrum of surface marker-based detection is especially conspicuous in kidney cancer, which is of mesodermal origin and expresses intrinsically low or no EpCAM. A number of other cancer types, including transitional cell carcinoma of the urinary bladder, squamous carcinoma of the skin, and hepatocellular carcinoma, have been known to express little EpCAM.…”
Section: Discussionmentioning
confidence: 99%